Religious freedom and the law: emerging contexts for freedom for and from religion - Scharffs, Brett G.; Maʿoz, Ašer; Woolley, Ashley Isaacson (ICLARS series on law and religion, 2019)
Thomas Farr / The ministerial exception : an inquiry into the status of religious freedom in the United States and abroad -- Pamela Slotte / The ministerial exception : theological and legal perspectives from Finland and Europe -- Frances Raday / Freedom from religion in international human rights law -- David Pollock / Is there a right to freedom from religion? -- Pierre Noël / Immigration as an experience of fundamental rights and religious freedom -- Sister Renée Mirkes / Healthcare conscience & competing sexual liberty claims -- Clemens Steinhilber / Preventing religious fundamentalism through higher education of faith leaders -- Maria Luisa Lo Giacco / Religious freedom and places of worship : religious buildings in Europe and in the United States -- Sarah Hayes / The religious precinct : the inequalities of equality law in religious property -- Jeroen Temperman / Freedom of/for/from religion in prison : a taxonomy of the Strasbourg jurisprudence -- Ahmed Salisu Garba / Islamic preaching board laws of Kano, Borno, and Niger States : a constitutional and human rights assessment -- Piotr Szymaniec / Freedom of religious beliefs or religious freedom? the recent case law of the polish constitutional tribunal -- Armin Langer / Christonormativity as religious neutrality : a critique of the concept of state religious neutrality in Germany -- Li-Ann Thio / Freedom of religion, conscience, and persuasion : international laws and perspectives from Asia -- Oscar Díaz Muñoz / Religious equality in the Peruvian constitution.